Effects of polytetrafluoroethylenemicro–particles on mechanical andtribological properties of glass fiberreinforced polyoxymethylene / Jasbir Singh Kunnan Singh - Jasbir Singh , Kunnan Singh (2020)
Reinforcing polyoxymethylene (POM) with glass fibers (GF) enhances its mechanical properties, but at the expense of tribological performance. Formation of a transfer film to facilitate tribo–contact is compromised due to the abrasiveness of GF. As a solid lubricant, for example, polytetrafluoroethylene (PTFE) significantly improves friction and wear resistance. The effects of chemically etched PTFE micro–particles on the fiber– matrix interface of POM/GF/PTFE composites have not been systematically characterized. This research investigated the effects of PTFE micro–particles on mechanical and tribological properties of POM/GF/PTFE composites. Since PTFE is immiscible with most polymers, the surface was etched using sodium naphthalene salt dissolved in tetrahydrofuran to increase its surface energy. The porous etching layer, characterized using Scanning Electron Microscopy (SEM) and Fourier Transform Infra– Red (FTIR) techniques promoted mechanical interlocking as the matrix melt filled these surface imperfections. The effects of two variables, namely PTFE content and PTFE etch time, on the mechanical properties of the composite were studied. Experiments were designed in accordance to response surface methodology (RSM) using central composite design (CCD). Samples were prepared with different contents of PTFE (1.7, 4.0, 9.5, 15.0, or 17.3 wt.%) at different PTFE etch times (2.9, 5.0, 10.0, 15.0, or 17.1 min). Four mechanical properties of the POM/GF/PTFE composites, that is, strength, stiffness, toughness, and hardness, were characterized as a function of two studied variables. The dependency of these mechanical properties on the PTFE etch conditions was analyzed using analysis of variance (ANOVA). Overall desirability, D global index, was computed based on the combination of these mechanical properties for POM/GF/PTFE composites. A continuous three–dimensional response surface plot with D global index as z–axis and the PTFE contents and PTFE etch times as x– and y–axis permitted a visual representation where desirability can be maintained at a high level over a range of the two predictors. The D global index was found to be 87.5%, when PTFE content and PTFE etch time were 6.5% and 10 min, respectively. Good correlation between experimental and RSM models was obtained using normal probability plots. These mechanical properties were evaluated by analyzing the fractured surfaces using SEM and the degree of crystallinity using Differential Scanning Calorimetry (DSC). Knowing these optimum conditions, tribological performance was characterized for POM/GF/PTFE composites as a function of micro–PTFE blended by weight percentage. Samples were prepared by different contents of PTFE (0, 1.7, 4.0, 9.5, 15.0 and 17.3 wt.%). The surface energy of PTFE micro–particles was increased by etching for 10 min using sodium naphthalene salt in tetrahydrofuran. Tribological performance was characterized through simultaneous acquisition of the coefficient of friction and wear loss on a reciprocating test rig in accordance to Procedure A of ASTM G133–95. Friction and wear resistance improved as the micro–PTFE weight ratio was increased. Morphology analysis of worn surfaces showed transfer film formation, encapsulating the abrasive GF. Energy dispersive X–ray spectroscopy (EDS) revealed increasing PTFE concentration from the GF surface interface region (0.5, 1.0, 1.5, 2.0, 2.5 μm).